Impact of COVID-19 Pandemic on Dental Education and Management - A.O. Arigbede (Nigerian Dental Association, 2020)
Objective: The coronavirus disease is a highly infectious disease of global concern. It poses a severe threat to the lives of patients, hospital staff, students, and their trainers. The impact of Covid-19 pandemic on dental education and management is diverse and deep. This study is designed to highlight the effects of COVID-19 pandemic on dental education and management. Materials and Methods: The Medline and google databases were searched for relevant publications by combining the following mesh terms, COVID-19, dental education, impact and residency. Relevant information was extracted from all the selected papers. Personal experience as a trainer, clinician and administrator was included in the report. Results: Because of the pandemic, patients flow nosedived, routine clinical procedures, academic activities, students/residents' rotation were suspended, and some of the students/ residents had their examinations or time of graduation postponed. The use of virtual platform became the norm for learning and meeting. A new and broader PPE protocol was prescribed when carrying out dental procedures. Residents and students must ensure physical distancing, even as it relates to the hanging of clothes in the changing room. Blended and self-directed learning was brought into the fore of medical education. Conclusion: Government and professional bodies should make conscious efforts to cushion the adverse effects of corona